PEMBERDAYAAN PETERNAK RUMINANSIA MELALUI PELATIHAN PEMBUATAN UREA MOLASSES BLOCK DI NAGARI PANGIAN KECAMATAN LINTAU BUO KABUPATEN TANAH DATAR - Ferry Lismanto Syaiful; Nasywa Pazain Harahap; Agustian Pratama (Jurnal Hilirisasi IPTEKS, 2025)
The aim of this initiative was to enhance the knowledge, skills, and independence of ruminant farmers in utilising local feed resources through training on the production of Urea Molasses Blocks (UMB) as a nutritious, cost-effective, and easily applicable feed supplement for smallholder livestock systems. The activity was conducted in Nagari Pangian, Lintau Buo Sub-district, Tanah Datar Regency, West Sumatra Province. This location was selected due to its relatively high population of ruminant livestock, yet limited access to quality feed. The methods applied included interactive lectures on the fundamentals of nutrition and the benefits of UMB, demonstrations of UMB production techniques, and hands-on practice by participants using locally available ingredients. A total of 30 active farmers participated, selected through coordination with local village authorities. Evaluation was carried out using pre- and post-tests to measure knowledge improvement, as well as a survey to assess participants’ responses and readiness to adopt the technology. The results showed that the average knowledge score increased from 55.3 to 83.7 after the training. Furthermore, 87% of participants expressed readiness to independently produce and utilise UMB. Most participants also reported that ingredients such as molasses, rice bran, and urea were easily accessible in their area. In conclusion, the activity proved effective in building farmer capacity, promoting the use of local potential, and supporting the development of locally based feed technologies for ruminant livestock in rural areas.